Effects of velocity-specific training on rate of velocity development, peak torque, and performance - Murray, D. P.; Brown, L. L.; Zinder, S. M.; Noffal, G. J.; Bera, S. G.; Garrett, N. M. (The Journal of Strength and Conditioning Research, 2007)
Little is known about the velocity-specific adaptations to training utilizing movement velocities in excess of 300 degrees x s(-1). The purpose of this investigation was to determine the effects of 4 weeks of slow (60 degrees x s(-1)) vs. fast (400 degrees x s(-1)) velocity training on rate of velocity development (RVD), peak torque (PT), and performance. Twenty male kinesiology students (22.0 years +/- 2.72; 178.6 cm +/- 7.1; 82.7 kg +/- 15.5) were tested, before and after 4 weeks of training, for PT production, RVD (at 60, 180, 300, 400, and 450 degrees x s(-1)), standing long jump (SLJ) distance, and 15- and 40-m sprint times. All participants underwent 8 training sessions, performing 5 sets of 5 repetitions of simultaneous, bilateral, concentric knee extension exercises on a Biodex System 3 isokinetic dynamometer at either 60 degrees or 400 degrees per second. Two 5 (speed) x 2 (time) x 2 (group) multivariate repeated measures analyses of variance revealed no significant differences between groups on any measure. Therefore, the groups were collapsed for analysis. There was a significant (p < 0.05) main effect for RVD by time and SLJ distance by time (pre- 227.1 cm +/- 21.2; post- 232.9 cm +/- 20.7) but no significant change in PT or 15- or 40-m sprint times. These results offer support for the suggestion that there is a significant neural adaptation to short-term isokinetic training performed by recreationally trained males, producing changes in limb acceleration and performance with little or no change in strength. Because results were independent of training velocity, it appears as though the intention to move quickly is sufficient stimulus to achieve improvements in limb RVD. Changes in SLJ distance suggest that open kinetic chain training may benefit the performance of a closed kinetic chain activity when movement pattern specificity is optimized.